EVALUATING THE EFFECT OF ISLAMIC FINANCING TO FINANCIAL DEVELOPMENT: EVIDENCE FROM OIC COUNTRIES - Selamah Maamor; Hafnida Hasan; Hussin Abdullah (International Journal of Management Studies, 2019)
The development of Islamic finance is governed by Islamic laws (Shariah). The main principles that regulate all forms of transactions in Islamic banking activities include the prohibition of interest or usury (riba),the use of excessive risk (gharar), and gambling (maysir). The Islamic finance industry has become a prominent sector and is one of the fastest growing components of financial developments over the last decade in the global financial system. The availability of large numbers of Islamic finance products will increase significantlyas there have been a growing demand throughout the world, especially in OIC participating countries. Hence, the objective of this study is to identify the important factors that enhances financial development in the selected OIC countries (Malaysia, Indonesia, Jordan, Kuwait, Saudi Arabia, Sudan and Yemen). Three indicators of financial development were used; Islamic finance, broad money and liquid liabilities. The data used in this study is the panel data from the year 1990 to 2012 which were obtained from the International Monetary Fund, Islamic Banks and Financial Institutions Information (IBIS), and World Bank databases. This study employed pooled OLS, fixed and random effect model. The results indicate that there are significant relationships between Islamic finance and financial development. Specifically, this study found that liquid liabilities and Islamic finance are two factors that have significantly influenced financial development in the OIC countries. Furthermore, the findings suggest that the OIC governments are required to develop policies that would integrate Islamic finance into their financial system. These policies should be centred around regulatory framework and supervisory role to utilize Islamic finance for greater economic growth. Keywords: Islamic finance; financial development; OIC countries; pooled OLS, fixed effect; random effect